Mazur G., Wegierski J. Konspiracja lwowska. 1939-1944: Slownik biograficzny - Ільюшин, І.І. (Український історичний журнал, 2001)
Рецензія на книгу: Mazur G., Wegierski J. Konspiracja lwowska. 1939-1944: Slownik biograficzny. - Katowice, 1997. - 255 s.